MO536: Cardiovascular Events in Patients With Anemia Associated With Non–Dialysis-Dependent Chronic Kidney Disease: Regional Analysis of Patients not Previously Treated With Erythropoiesis-Stimulating Agents in The PRO2TECT Trial. (3rd May 2022) - Winkelmayer, Wolfgang; Arnold, Susan; Burke, Steven; Chertow, Glenn; Eckardt, Kai-Uwe; Luo, Wenli; Minga, Todd; Parfrey, Patrick
Abstract: BACKGROUND AND AIMS: Vadadustat is an oral hypoxia-inducible factor prolyl hydroxylase inhibitor being investigated for treatment of anemia due to chronic kidney disease (CKD). In global phase 3 trials, vadadustat has demonstrated non-inferiority to darbepoetin alfa for time to major adverse cardiovascular event (MACE) in patients with dialysis-dependent CKD (INNO2 VATE trials), but not with non–dialysis-dependent CKD (NDD-CKD; PRO2 TECT trials) [1, 2 ]. In a prespecified subgroup analysis of the PRO2 TECT trials, no difference in cardiovascular safety was observed in the USA, but a higher risk of MACE was found for patients treated with vadadustat outside the USA. 1 We investigated regional differences in MACE in patients previously untreated with erythropoietin-stimulating agents (ESAs) in the PRO2 TECT trial. METHOD: Two phase 3, open-label, randomized, active-controlled clinical trials comparing vadadustat with darbepoetin alfa were conducted in North America, Latin America, Europe, Africa, and the Asia-Pacific region. This post hoc analysis evaluated MACE in patients in the PRO2 TECT trial not treated with ESAs within 8 weeks of enrollment (correction trial; NCT02648347) and who received ≥1 dose of trial drug, stratified by region (USA versus Europe versus non-USA/non-Europe). MACE was defined as a composite of death from any cause, nonfatal myocardial infarction, or nonfatal stroke. Expanded MACE was defined as MACE plus hospitalization for heart failure or thromboembolic event, excluding vascular access failure. RESULTS: A total of 1748 ESA-untreated patients receiving ≥1 dose of study drug were enrolled in the PRO2 TECT trial, including 1058 patients in the USA, 139 in Europe and 551 outside the USA and Europe. Patients in the non-USA/non-European countries were younger and had a lower mean eGFR than patients in the USA or Europe. Furthermore, 34.7% of patients randomized to vadadustat had a baseline eGFR <10 mL/min/1.73 m 2 versus 24.0% of patients randomized to darbepoetin alfa in the non-USA/non-European countries. The hazard ratio for MACE in the overall population for vadadustat versus darbepoetin alfa was 1.16 [95% confidence interval (CI) 0.96–1.41]. When analyzed by region, higher event rate for MACE was observed in the vadadustat arm in the non-USA/non-European countries compared with the USA and Europe (Table 1 ). The higher event rates for MACE in the non-USA/non-European countries were driven by 21 excess MACEs reported in the vadadustat group. Many deaths in the non-USA/non-European countries were related to kidney failure ( n  = 25/43 in the vadadustat group; n  = 20/30 in the darbepoetin alfa group; Table 2 ), and were concentrated in Brazil and South Africa, countries that enrolled a higher proportion of patients with end-stage kidney failure who may not have had access to dialysis. The adverse event profiles for vadadustat and darbepoetin alfa were similar across regions. CONCLUSION: Regional differences in time to first MACE were observed in patients with NDD-CKD who were not previously treated with ESAs and randomized to receive vadadustat or darbepoetin alfa as part of the PRO2 TECT trial. The higher event rate in the vadadustat group in non-USA/non-European countries may have been related to randomization imbalances and/or design and methodological issues. These findings should help inform care providers as they assess the overall safety of vadadustat for the treatment of anemia associated with NDD-CKD.